The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13173760
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Green Diatomite/Chitosan-Based Hybrid Foams with Dye Sorption Capacity

Abstract: The latest tendency of the scientific community regards the development of different classes of green materials able to solve pollution problems caused by industrial and human activity. In this paper, chitosan and diatomite were used to produce a broad-spectrum hybrid adsorbent, either in powder or in monolithic form for environmental pollutant removal. Diatomite–chitosan-based powders and porous diatomite–chitosan hybrids were prepared and characterized by chemical-physical, thermal and morphological analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, the dye uptake test revealed uptake of the solution of 1-1 methylene blue in ethanol due to the color changing from white to blue. This indicated that the capillary effect enabled the absorption of the solution into the foam, thus confirming the open cellularity [ 101 , 102 , 103 ].…”
Section: Resultsmentioning
confidence: 69%
“…Furthermore, the dye uptake test revealed uptake of the solution of 1-1 methylene blue in ethanol due to the color changing from white to blue. This indicated that the capillary effect enabled the absorption of the solution into the foam, thus confirming the open cellularity [ 101 , 102 , 103 ].…”
Section: Resultsmentioning
confidence: 69%
“…The FT-IR spectrum of chitosan-diatomaceous earth hybrid before adsorption has well dened peaks at 1089 cm À1 which is indicative of the C-O skeletal vibrations and at 3116-3268 cm À1 reecting the N-H and O-H stretching band vibrations. 43 As obvious 2883 cm À1 is a characteristic trait of C-H stretching vibration. Vibrations at 1660 cm À1 corresponds to C]O stretching of amide bond.…”
Section: Surface Features Of the Chitosan-diatomaceous Earth Adsorbentmentioning
confidence: 99%
“…Vibrations at 1660 cm À1 corresponds to C]O stretching of amide bond. The Si-O and Si-O-Si groups 43,44 and the deformations are observed around 620 cm À1 . The FTIRspectra aer adsorption of 4,4 0 -DDT showed a denite shi in N-H vibrational frequency to 3268 cm À1 indicating that the amine groups are indeed involved in the interaction mechanism.…”
Section: Surface Features Of the Chitosan-diatomaceous Earth Adsorbentmentioning
confidence: 99%
“…However, the obtained chitosan-based materials are mostly powder, which is easy to block and complicated to reuse in the face of common separation methods. 20,21 Thus, non-traditional chitosan adsorbents including beads, 22 fibers, 23 and foams 24 are developed to overcome the above-mentioned problems. These adsorbents with various morphologies have mechanical strength to some extent but have shortcomings such as weak elasticity and difficulty in generating micropores.…”
Section: Introductionmentioning
confidence: 99%